2008
DOI: 10.1111/j.1600-0854.2008.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

The Itinerary of Autophagosomes: From Peripheral Formation to Kiss‐and‐Run Fusion with Lysosomes

Abstract: Macroautophagy, a constitutive process in higher eukaryotic cells, mediates degradation of many long-lived proteins and organelles. The actual events occurring during the process in the dynamic system of a living cell have never been thoroughly investigated. We aimed to develop a live-cell assay in which to follow the complete itinerary of an autophagosome. Our experiments show that autophagosomes are formed randomly in peripheral regions of the cell. They then move bidirectionally along microtubules, accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
352
3
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(399 citation statements)
references
References 30 publications
37
352
3
4
Order By: Relevance
“…We isolated APG (enriched in LC3‐II and p62; note that the low amounts of LAMP1 and cathepsin observed in this fraction could represent amphisomes [resulting from fusion of APG and late endosomes]) and AUT (also enriched in both markers but with higher abundance of lysosomal markers (LAMP1, CathB, and mucolipin; Figure 4a ). To determine whether our isolation procedure preserved vesicle‐associated motor proteins, we performed immunoblots for the minus‐end‐directed motor dynein (Jahreiss et al., 2008; Katsumata et al., 2010; Kimura, Noda & Yoshimori, 2007; Kimura et al., 2008) and the plus‐end‐directed motor KIF5B (Cardoso et al., 2009; Geeraert et al., 2010) previously described to contribute to trafficking of autophagic compartments. Immunofluorescence and immunoblot for motor proteins (dynein shown in Figure 4a,b and S4a–c) in the isolated fractions confirmed that motors were indeed present on the surface of the isolated APG and were not due to contamination of the preparation with cytosol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We isolated APG (enriched in LC3‐II and p62; note that the low amounts of LAMP1 and cathepsin observed in this fraction could represent amphisomes [resulting from fusion of APG and late endosomes]) and AUT (also enriched in both markers but with higher abundance of lysosomal markers (LAMP1, CathB, and mucolipin; Figure 4a ). To determine whether our isolation procedure preserved vesicle‐associated motor proteins, we performed immunoblots for the minus‐end‐directed motor dynein (Jahreiss et al., 2008; Katsumata et al., 2010; Kimura, Noda & Yoshimori, 2007; Kimura et al., 2008) and the plus‐end‐directed motor KIF5B (Cardoso et al., 2009; Geeraert et al., 2010) previously described to contribute to trafficking of autophagic compartments. Immunofluorescence and immunoblot for motor proteins (dynein shown in Figure 4a,b and S4a–c) in the isolated fractions confirmed that motors were indeed present on the surface of the isolated APG and were not due to contamination of the preparation with cytosol.…”
Section: Resultsmentioning
confidence: 99%
“…Since the role of the minus‐end‐directed motor dynein in retrograde APG trafficking has been well stablished (Jahreiss et al., 2008) and lysosome‐associated KIFC2 did not significantly change with age (Figure 4e,f) and was almost absent in primary fibroblasts (Figure S3d), we set instead to understand the contribution of KIFC3 (the most ubiquitous member of the C‐kinesin family) to the aging‐autophagy phenotype because (i) we found that KIFC3 was highly enriched in purified lysosomes (Figure 4f), (ii) its levels were markedly reduced in this compartment in liver from old mice (Figure 4f), and (iii) starvation, at least partially, restored KIFC3 levels in lysosomes (Figure 4f). Three‐dimensional reconstruction of young primary fibroblasts costained for KIFC3 and cathepsin D (Figure 5a) or LAMP1 (Figure 5b) confirmed that, as was the case in liver, KIFC3 was also associated with lysosomes in fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microtubules organize the formation of autophagosomes, their transport, and subsequent fusion events [5456] by electrostatic interactions originating from the N-terminal domain of LC3 thereby allowing the attachment of autophagosomes to the microtubule network [57,58]. Chemical disruption of microtubules reduces the formation of mature autophagosomes [55].…”
Section: Discussionmentioning
confidence: 99%
“…Dynactin 1 (DCTN1), another ALS-causing gene (Puls et al, 2003), mediates the transfer of autophagosome within the cell to facilitate fusion with lysosomes (Jahreiss et al, 2008;Kimura et al, 2008). In Perry syndrome, a complex neurodegenerative disease manifesting mainly with parkinsonism and caused by specific DCTN1 mutations, autophagic impairment is suggested by neuronal aggregates containing p62 in autoptic specimens (Farrer et al, 2009).…”
Section: Accumulation Of Als Pathogenetic Proteins and Autophagymentioning
confidence: 99%